Restricting digital sites of dissent: commercial social media and free expression. Issue 3 (26th May 2016) - Hintz, Arne
ABSTRACT: The widespread use of commercial social media platforms by protesters and activists has enhanced protest mobilisation and reporting but it has placed social media providers in the intermediary role as facilitators of dissent and has thereby created new challenges. Companies like Google and Facebook are increasingly restricting content that is published on or distributed through their platforms; they have been subject to obstruction by governments; and their services have been at the core of large-scale data collection and surveillance. This article analyses and categorises forms of infrastructure-based restrictions on free expression and dissent. It shows how private intermediaries have been incorporated into state-led content policies; how they set their own standards for legitimate online communication and intervene accordingly; and how state-based actions and commercial self-regulation intersect in the specific area of online surveillance. Based on a broad review of cases, it situates the role of social media in the wider trend of the privatisation of communications policy and the complex interplay between state-based regulation and commercial rule-making.